Dynamic patterns of communication and workload during cardiac surgery: An explorative study - Liam Wietzorrek; Eugenie Craenen; Indy van Boven; Massimo A. Mariani; Fokie Cnossen (PLoS ONE, 2026)
Background Effective communication amongst operating room (OR) teams is crucial for ensuring patient safety and optimizing surgical outcomes. This study aimed to investigate communication within the context of physiologically assessed workload during cardiac surgeries. Specifically, the relationship between team members’ workload and both case-relevant and case-irrelevant communication exchanges was explored, as well as their association with the length of surgical phases. Methods Intraoperative communication exchanges were annotated from incision until skin closure across 24 recorded cardiac surgeries (>100h surgery time). OR team members wore heart rate monitors throughout the surgical procedures. HRV was calculated as the RMSSD across 5-minute non-overlapping windows. Mixed effect models were used to assess the relationship between workload and the frequency of communication exchanges across OR roles and surgical phases. Results Relevant communication was most frequent during the initiation and discontinuation of extracorporeal bypass, while case-irrelevant communication was most frequent during the final closing phase of surgery. Team members were more likely to engage in case-irrelevant communication during periods of reduced workload ( χ 2 = 30.15, p = .001). However, this did not necessarily align with the workload of other team members, as increased workload was associated with more frequent case-irrelevant communication initiated by other team members ( χ 2 = 5.97, p = .015). Workload and case-relevant communication had a significant effect on surgical phase length. Conclusions The findings highlight the dynamic relationship between workload and intraoperative communication patterns. Integrating observational data with physiological indicators of workload appears a promising approach to studying team dynamics in the operating room, though further research is needed to advance the use of such methods for improving team performance.